2012
DOI: 10.1007/s00259-012-2110-3
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of two 68Ga-siderophores as potential radiopharmaceuticals for Aspergillus fumigatus infection imaging

Abstract: PurposeInvasive pulmonary aspergillosis is mainly caused by Aspergillus fumigatus, and is one of the major causes of morbidity and mortality in immunocompromised patients. The mortality associated with invasive pulmonary aspergillosis remains high, mainly due to the difficulties and limitations in diagnosis. We have shown that siderophores can be labelled with 68Ga and can be used for PET imaging of A. fumigatus infection in rats. Here we report on the further evaluation of the most promising 68Ga-siderophore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
117
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 37 publications
5
117
0
Order By: Relevance
“…Siderophore biosynthetic enzymes are also upregulated in conidia internalized by airway epithelial cells (Oosthuizen et al, 2011). Aspergillus fumigatus has been reported to utilize xenosiderophores including ferrichrome, coprogen, ferrioxamine B and ferrioxamine E (Petrik et al, 2012). Candida albicans, also a frequent colonizer in CF (Chotirmall et al, 2010), has been reported to produce both hydroxamateand phenolate-type siderophores (Holzberg & Artis, 1983;Ismail et al, 1985); however, siderophore biosynthesis genes have not been identified in the Candida albicans genome (Haas, 2003).…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…Siderophore biosynthetic enzymes are also upregulated in conidia internalized by airway epithelial cells (Oosthuizen et al, 2011). Aspergillus fumigatus has been reported to utilize xenosiderophores including ferrichrome, coprogen, ferrioxamine B and ferrioxamine E (Petrik et al, 2012). Candida albicans, also a frequent colonizer in CF (Chotirmall et al, 2010), has been reported to produce both hydroxamateand phenolate-type siderophores (Holzberg & Artis, 1983;Ismail et al, 1985); however, siderophore biosynthesis genes have not been identified in the Candida albicans genome (Haas, 2003).…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…20 Nuclear imaging techniques, such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT), have also been used for detecting pulmonary aspergillosis in rodents by using radioactive probes. 21,22 As the use of radioactive tracers requires their production in cyclotrons, PET and SPECT may not always be the most practical methods for a preclinical setting. Also, the selectivity of PET tracers, such as 68 Ga-siderophores and 89 Zr-oxalate, for detecting Aspergillus infections has yet to be investigated in more detail.…”
mentioning
confidence: 99%
“…Also, the selectivity of PET tracers, such as 68 Ga-siderophores and 89 Zr-oxalate, for detecting Aspergillus infections has yet to be investigated in more detail. 21,23 Computed tomography (CT) is highly suitable for lung applications because it produces high-resolution 3D images (o100 μm) with an excellent air-tissue contrast. 24,25 The value of this imaging technique has been studied in disease models of lung fibrosis, lung emphysema and lung neoplasms.…”
mentioning
confidence: 99%
“…Petrik and colleagues demonstrated clinical use in imaging pulmonary aspergillosis (89). Mouse and rat infection models were developed and siderophores (triacetylfusarinine and ferrioxamine E) were labeled with gallium 68 ( 68 Ga).…”
Section: Pharmacological and Medical Applicationsmentioning
confidence: 99%